The Evolving Contribution of R&D, Advertising and Capital Expenditures for US-Listed Firms' Growth in Sales, 1979-2018 - Joel Rabinovich (City, University of London, City Political Economy Research Centre (CITYPERC), 2022)
This article presents new insights on the evolving contribution of di!erent types of investments to the growth in sales of US non"nancial listed "rms during the 1979-2018 period. By means of quantile regressions it is observed an increasing contribution over time of intangible investment vis-à-vis a decline in capital expenditure both for high-growth and slow-growth "rms. However, the impact of di!erent types of intangible investment di!ers depending on the kind of "rm. Whereas research and development (R&D) has a positive contribution for highgrowth "rms, only advertising has a positive e!ect for their slow-growth peers.
Keywords: 330; Firm growth; Fast-growth firms; Quantile Regression; Intangibles